The Dimensions of Erich Fromm’s Concept of Love in Andrea Hirata’s Novel Father - Sri Yustina; Herlandri Eka Jayaputri; Muhammad Fahruddin Aziz (Yayasan Kyadiren, 2025)
This study explores the representation of five types of love objects as conceptualised in Erich Fromm’s theory—love for others, maternal love, erotic love, self-love, and love for God—in Andrea Hirata’s novel “Ayah”. Employing a qualitative literary psychology approach with content analysis techniques, the study identified and analysed 38 instances that illustrate various forms of love. The findings reveal the predominance of love for others and erotic love in shaping character dynamics and driving the narrative. The character Sabari emerges as a symbol of transcendental love characterised by sacrifice and sincerity. Furthermore, the study demonstrates that the values of love depicted in the novel reflect the complexity of Indonesian emotional and cultural expressions. Theoretically, this study contributes by broadening the understanding of the concept of love in Indonesian literature through Fromm’s framework, whilst reinforcing the pertinence of literary psychology in the analysis of local fiction.